ダイ 26 ジ ニホン ナンキョク チイキ カンソク タイ エンガン チョウサ リョコウ ホウコク 1985 - 村山, 治太; ムラヤマ, ハルタ; Murayama, Haruta (1987)
P(論文) 第26次日本南極地域観測隊は越冬期間中に, リュツォ・ホルム湾東岸の露岩地帯および島へ, 環境モニタリングのための旅行を28回実施した。4月中旬に海氷が流失したために, ルート工作が大幅に遅れ, 初めてラングボブデまで行くことができたのが7月15日, スカーレンまでのルートができたのは8月13日だった。湖沼水モニタリングは1978年に定められた5定点のほかにすりばち池(スカルブスネス地域)を追加し, 湖沼水の季節変化を追求した。大型動物センサスはアデリーペンギンの個体数の計数を主目的とした。本報告では行動経過, 設営の概要など第26次越冬隊で実施した沿岸調査旅行の概要について述べる。 The coastal research trips were frequently carried out by the 26th Japanese Antarctic Research Expedition members for monitoring the Antarctic environment. The research area was the east coast of Lutzow-Holm Bay. The scientific aims of these trips were the study of five ponds which were selected as the monitoring stations in 1978,and the census of Adelie penguins and seals. In the present paper an outline of the trips is reported. departmental bulletin paper